The Overview of Chemical Knowledge in Eighteenth Century Georgia According to the Chemistry Book by King Vakhtang VI - Kupatadze, Ketevan; Malazonia, David; Gverdtsiteli, Michael (Orbital: The Electronic Journal of Chemistry, 2016)
The article deals with political and educational-cultural situation in Georgia during the reign of King Vakhtang VI (XVIII century). It describes the book on chemistry compiled and published by Vakhtang VI. The methods of chemical experiments highlighted in the book are compared to the methods of early alchemists, such as: Jābir ibn Hayyān, Muhammad ibn Zakariyā Rāzī, Liebau and others. The article summarizes the methods to which Vakhtang VI agreed and also indicates the techniques, slightly differently presented in his records. The paper also points out how the King could get information on chemistry. It gives an assumption that the scientific information most likely was brought by travelers who were close to the king or was accumulated from the early period and was also linked with journeys.DOI: http://dx.doi.org/10.17807/orbital.v8i3.839